Sensitivity of summer precipitation to tropical sea surface temperatures over East Asia in the GRIMs GMP. Issue 9 (15th May 2013) - Chang, Eun‐Chul; Yeh, Sang‐Wook; Hong, Song‐You; Wu, Renguang
Abstract [1] In this study, uncoupled atmospheric general circulation model experiments are conducted to examine the sensitivity of tropical Ocean basins from the Indian Ocean to the tropical Pacific Ocean on the summer precipitation variability over East Asia. It is remarkable that the Indian Ocean basin sea surface temperature (SST) and the tropical Pacific basin SST act on summer precipitation variability over Northeast Asia and southern China quite differently. That is, SST warming in the Indian Ocean largely contributes to the increase in the amount of summer precipitation over East Asia, which is in contrast to the warming of the western tropical Pacific Ocean. Our further analysis indicates that an altered large‐scale atmospheric circulation over the western tropical Pacific contributes to contrasting atmospheric motion over East Asia due to the tropics‐East Asia teleconnections, which results in changes in the amount of summer precipitation due to the warming of the Indian and western tropical Pacific Oceans.